1999
DOI: 10.1161/01.cir.99.17.2290
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism Associated With an Inherited Cardiac Arrhythmia

Abstract: Our results from both the Xenopus oocyte and HEK293 cell expression systems and green fluorescent protein tagging and Western blot analyses support the conclusion that the G601S mutant is a hypomorphic mutation, resulting in a reduced current amplitude. Thus, it represents a novel mechanism underlying LQT2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(95 citation statements)
references
References 26 publications
4
90
1
Order By: Relevance
“…Western blot analyses of WT hERG overexpression in several systems, including HEK-293 cells, have shown two protein bands at 135 kDa (immature) and 155 kDa (mature) that represent posttranslational core and complex glycosylation of hERG protein, respectively (2,15,19,45). We next transfected the missense mutations, G601S and N470D hERG (12,16,36), that form trafficking-deficient channel proteins when studied in noncardiac mammalian systems (3,16,45). Western blot analysis in the cardiomyocytes showed that G601S and N470D hERG generate 135-kDa protein bands but only weak or no 155-kDa protein bands, indicating that for control conditions these two mutations generate immature protein that then does not undergo normal Golgi processing to the mature protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analyses of WT hERG overexpression in several systems, including HEK-293 cells, have shown two protein bands at 135 kDa (immature) and 155 kDa (mature) that represent posttranslational core and complex glycosylation of hERG protein, respectively (2,15,19,45). We next transfected the missense mutations, G601S and N470D hERG (12,16,36), that form trafficking-deficient channel proteins when studied in noncardiac mammalian systems (3,16,45). Western blot analysis in the cardiomyocytes showed that G601S and N470D hERG generate 135-kDa protein bands but only weak or no 155-kDa protein bands, indicating that for control conditions these two mutations generate immature protein that then does not undergo normal Golgi processing to the mature protein.…”
Section: Resultsmentioning
confidence: 99%
“…WT hERG with appropriate nucleotide changes (⌬TAC2342-2344) resulting in ⌬Y475 hERG was generated using site-directed mutagenesis and verified by DNA sequencing. G601S and N470D hERG were generated as previously described (16,45). hERG cDNAs for neonatal mouse cardiomyocyte experiments were generated as endotoxin free using the EndoFree Plasmid Maxi Kit (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…To directly address whether TRC8 selects misfolded populations of hERG for degradation, we studied the LQT2 pore mutation G601S and the CNBD mutation F805C, both of which cause misfolding and ERAD (3)(4)(5)(6). Growth at 27°C allows some folding and trafficking of hERG-G601S, albeit inefficiently compared with WT (5).…”
Section: Trc8 Promotes Degradation Of Misfolded Mutant Herg-g601s-mentioning
confidence: 99%
“…The hERG polypeptide contains N-and C-terminal cytosolic domains around a central transmembrane region that tetramerizes to form the channel pore, implicating cytosolic and transmembrane factors in quality control. LQT2 mutations that disrupt folding are found throughout the hERG sequence, for example G601S in the pore region and F805C in the C-terminal cyclic nucleotide binding domain (CNBD) (3)(4)(5)(6). The chaperone Hsp90 is necessary for hERG trafficking (7).…”
mentioning
confidence: 99%
“…Some familial forms of LQT syndrome are caused by the production of mutant hERG proteins that are inappropriately retained in the ER (26)(27)(28). Remarkably, this deficit can sometimes be overcome by treatment with certain hERGbinding drugs that somehow promote the subsequent processing and transport of the mutant channels to the plasma membrane, where they function normally (26,29,30).…”
Section: Discussionmentioning
confidence: 99%